Physicochemical Characterization and Asymmetric Catalytic Properties of New Biobased Organocatalytic Surfactants - Elliot Calbrix; Pascale de Caro; Sophie Thiebaud-Roux; Christine Cecutti; Emeline Vedrenne (Molecules)
In organic synthesis, the solvent is the chemical compound that represents the largest proportion of the process. However, conventional solvents are often toxic and dangerous for the environment, and an interesting alternative is to replace them by water. In this context, catalyst surfactants allow both organic reagents in water to be solubilized and organic reactions to be catalyzed. This article describes the synthesis of new biobased organocatalytic surfactants soluble in water, composed of a hydrocarbon chain grafted onto an imidazolidinone moiety. The imidazolidinone moiety acts as catalyst, but also as the polar head of the surfactant, while the fatty chain constitutes the hydrophobic tail. The five steps of the synthesis were optimized, respecting the principles of green chemistry, and two organocatalytic surfactants were obtained with a good selectivity. Surface properties in an aqueous medium were then evaluated with the use of tensiometric analysis. Their molecular organization in vesicles was characterized by Dynamic Light Scattering. The presence of vesicles allows reactions to be carried out in an organized aqueous medium. Model catalytic reactions performed in aqueous medium validated the feasibility of replacing conventional hazardous organic solvents. The newly synthesized biobased surfactants showed satisfactory catalytic activity and allowed the expected products to be obtained with good enantioselectivity.